Indigenous epistemologies and intercultural ethics: An ethicological reading of the fifth chapter of the Huarochirí Manuscript - Beauclair, Nicolas (2009)
This article is an ethicological reading of chapter 5 of the Huarochirí Manuscript (Taylor ed. and trans. 1999), a Peruvian colonial writing from the 17th century. The analysis wants to demonstrate that the stories from the oral tradition can be a valid source for the study of the ethics of the indigenous peoples of America, that is, the values ​​and norms that guide their way of relating between human beings and with non-human beings. humans. The study of these ethics seeks to be carried out in the perspective of the creation of intercultural ethics that respond to the coloniality of knowledge and that could contribute to the debates that concern the current globalization and the management of its different processes. Specifically, our analysis resorts to a methodological procedure coming from various theoretical currents, among which Latin American colonial studies, discourse analysis and ethicology stand out. We will start the article with some general considerations about the work in question, which will allow us to understand its textual and discursive construction; Next, we will proceed to the analysis of Chapter 5 of the Manuscript, as well as its ethical interpretation. The analysis concludes that the Manuscript reveals an "ethics of reciprocity" and that this could be useful to rethink ethics and intercultural relations in the current era of globalization.